2022
DOI: 10.1101/2022.02.10.479953
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Machine learning-assisted discovery of growth decision elements by relating bacterial population dynamics to environmental diversity

Abstract: Microorganisms growing in their habitat constitute a complex system. How the individual constituents of the environment contribute to microbial growth remains largely unknown. The present study focused on the contribution of environmental constituents to population dynamics via a high-throughput assay and data-driven analysis of a wild-type Escherichia coli strain. A large dataset constituting a total of 12,828 bacterial growth curves with 966 medium combinations, which were composed of 44 pure chemical compou… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 77 publications
0
14
0
Order By: Relevance
“…The enrichment of the single resource of glucose and the overall nutritional richness (LB) in the media resulted in the reverse directional changes in the colony size. This result strongly suggested that the balance of the medium composition largely participated in colony growth, as similar as to population growth in liquid media (Ashino et al, 2019;Aida et al, 2022). In addition, the coefficient of variation of colony size (V k ), kurtosis (U k ), and skewness (Z k ) of the size distribution of colonies all remained roughly comparable (p > 0.05), independent of either genome reduction or nutritional variation (Figure 3B).…”
Section: Genomic and Nutritional Differences Correlated With Colony S...mentioning
confidence: 70%
“…The enrichment of the single resource of glucose and the overall nutritional richness (LB) in the media resulted in the reverse directional changes in the colony size. This result strongly suggested that the balance of the medium composition largely participated in colony growth, as similar as to population growth in liquid media (Ashino et al, 2019;Aida et al, 2022). In addition, the coefficient of variation of colony size (V k ), kurtosis (U k ), and skewness (Z k ) of the size distribution of colonies all remained roughly comparable (p > 0.05), independent of either genome reduction or nutritional variation (Figure 3B).…”
Section: Genomic and Nutritional Differences Correlated With Colony S...mentioning
confidence: 70%
“…The remaining 28 components were changed from zero to 10~100 folds of their concentrations in EMEM. In brief, four to five different concentrations were used for each component, and the changes were roughly on a logarithmic scale, as described previously 30 . The medium combinations were prepared by mixing the stock solutions of individual components, prepared at high concentrations in advance, as described previously 30 .…”
Section: Preparation Of Medium Combinationsmentioning
confidence: 99%
“…In brief, four to five different concentrations were used for each component, and the changes were roughly on a logarithmic scale, as described previously 30 . The medium combinations were prepared by mixing the stock solutions of individual components, prepared at high concentrations in advance, as described previously 30 . The stock solutions were sterilized by the sterile syringe filters (Merck) with hydrophilic PVDF membranes of 0.22 µm pore size and were dispensed in a small volume and stored at -20°C for future use.…”
Section: Preparation Of Medium Combinationsmentioning
confidence: 99%
See 2 more Smart Citations